Lead Telluride Doped with Au as a Very Promising Material for Thermoelectric Applications - Pantelija M. Nikolic; Konstantinos M. Paraskevopoulos; Triantafyllia T. Zorba; Zorka Z. Vasiljevic; Eleni Pavlidou; Stevan S. Vujatovic; Vladimir Blagojevic; Obrad S. Aleksic; Aleksandar I. Bojicic; Maria V. Nikolic (Advances in Materials Science and Engineering)
PbTe single crystals doped with monovalent Au or Cu were grown using the Bridgman method. Far infrared reflectivity spectra were measured at room temperature for all samples and plasma minima were registered. These experimental spectra were numerically analyzed and optical parameters were calculated. All the samples of PbTe doped with Au or Cu were of the “n” type. The properties of these compositions were analyzed and compared with PbTe containing other dopants. The samples of PbTe doped with only 3.3 at% Au were the best among the PbTe + Au samples having the lowest plasma frequency and the highest mobility of free carriers-electrons, while PbTe doped with Cu was the opposite. Samples with the lowest Cu concentration of 0.23 at% Cu had the best properties. Thermal diffusivity and electronic transport properties of the same PbTe doped samples were also investigated using a photoacoustic (PA) method with the transmission detection configuration. The results obtained with the far infrared and photoacoustic characterization of PbTe doped samples were compared and discussed. Both methods confirmed that when PbTe was doped with 3.3 at% Au, thermoelectric and electrical properties of this doped semiconductor were both significantly improved, so Au as a dopant in PbTe could be used as a new high quality thermoelectric material.